Carotid IMT is more associated with stroke than risk calculators (2015)
Background – It is unclear whether a natural marker of atherosclerosis (carotid intima-media thickness: CIMT) or calculated risk score is more associated with stroke. We therefore comparatively examined the relationship between CIMT as well as two cardiovascular risk calculators (Omnibus Risk Score -ORS and Framingham Risk Score- FRS) and the occurrence of stroke among hypertensive African patients. Methods – CIMT was measured in 555 consecutive consenting hypertensive adults (377 stroke patients and 178 strokefree subjects). The 10-year cardiovascular risk was calculated for each participant with the FRS and ORS. The strengths of association between FRS, ORS, CIMT, and stroke occurrence were examined using logistic regression. The discriminative capacity of FRS, ORS, and CIMT for stroke occurrence was assessed with c-statistics. Results – Higher average CIMT (OR 11.71; 95% CI 1.65–83.07; P = 0.01) was strongly associated with stroke after adjusting for age, sex, blood pressure, serum cholesterol, and blood sugar. Neither the FRS (OR: 1.03; CI: 0.89–1.19, P = 0.68) nor the ORS (OR: 1.08; CI: 0.90–1.30; P = 0.41) was significantly associated with stroke. CIMT had a higher c-statistic for differentiating stroke patients from hypertensive controls (right: c = 0.63, P < 0.001; left: c = 0.67, P < 0.001; average: c = 0.66, P < 0.001) than some conventional risk factors. Neither FRS (P = 0.39) nor ORS (P = 0.55) was able to independently differentiate between stroke and hypertensive patients. Conclusion – CIMT, but neither FRS nor ORS, is independently associated with stroke among Nigerian African hypertensive patients. CIMT may be a better tool for estimating the overall risk of stroke than FRS or ORS in this population.